Outbreak of systemic Candida albicans in intensive care unit caused by cross infection. Issue 6470 (9th March 1985) - Burnie, J P; Odds, F C; Lee, W; Webster, C; Williams, J D
Abstract : The first documented outbreak of systemic candidosis shown to be due to cross infection with a particular strain of Candida albicans is reported. Over nine months in an intensive care unit 13 patients developed definite and one probable systemic candidosis. Twenty five further patients had superficial candidal infections. The strain that caused the outbreak (serotype A, morphotype A1, biotype 0/(1)5 5/7) was responsible for all the cases of systemic candidosis acquired in the intensive care unit, 11 (44%) of the superficial candidal infections in the unit, and 17% of candidal infections outside the unit but in the same hospital. The strain was also isolated from oral swabs taken from four nurses working in the unit and the hands of one of these nurses. Two out of 17 nurses were shown to have acquired the strain on their hands when examined immediately after nursing systemically infected patients. No environmental source could be identified. The strain also showed enhanced survival in handwashing experiments and was relatively resistant to Hibiscrub. Management of patients with systemic candidosis might include measures to prevent cross infection and handwashing with disinfectants that are active against candida.